The Implementation of Text-Based Approach Within the Merdeka Curriculum in Junior High School - Intania, Annisa; Jannah, Nur Miftahul; Sari, Putri Nilam; Hasibuan, Kalayo (Jurnal Kajian Ilmu Pendidikan (JKIP), 2024)
This paper explores the implementation of a text-based approach in the Merdeka Curriculum within junior high schools. The Merdeka Curriculum is a new educational program in Indonesia that aims to promote critical thinking and independence among students. The text- based approach emphasizes the use of texts as the main learning resource, focusing on reading, analyzing, and synthesizing information to develop students' cognitive abilities, psychomotor and social. This study assesses the effectiveness of implementing the text-based approach within the Merdeka Curriculum in junior high schools and its impact on students' learning outcomes.